Amperometric Detection of Apoptosis by using p‐Methoxyaniline‐Conjugated Substrate for Caspase‐3. Issue 4 (16th March 2017) - Sixiang, Sun; Inoue, Kumi Y.; Shiomoto, Shusaku; Takano, Shinichiro; Ino, Kosuke; Shiku, Hitoshi; Matsue, Tomokazu
Abstract: This manuscript reports on a novel substrate for the amperometric detection of cellular apoptosis, Asp‐Glu‐Val‐Asp‐ p ‐methoxyaniline (DEVD‐ p MA). This substrate showed electrochemical inertia from −0.2 to 0.7 V versus Ag/AgCl in phosphate‐buffered saline (PBS), but was cleaved by caspase‐3, releasing p MA, which was detected with cyclic voltammetry and chronoamperometry. Compared with p ‐aminophenol ( p AP), p MA showed lower toxicity to the human hepatocellular carcinoma cell line (HepG2) and higher stability in PBS. By using this substrate, we successfully detected caspase‐3 in the range of 0.31–2.5×10 −2 units/mL and cellular apoptosis in HepG2 cells by using simple amperometry without cell lysis. This work will help to develop a simple method for the electrochemical monitoring of apoptosis, which can be applied in biological research and drug development. Abstract : Electric current tells cell apoptosis : A novel caspase‐3 substrate, Asp‐Glu‐Val‐Asp‐ p ‐methoxyaniline (DEVD‐ p MA), is developed for simple amperometric detection of cellular apoptosis. This substrate is cleaved by caspase‐3, releaseing the p MA molecule, which can be detected with amperometry. By using DEVD‐ p MA, caspase‐3 is successfully detected in the range of 0.31–2.5×10 −2 units/mL. Cellular apoptosis in HepG2 cells is also detected through simple amperometry without cell lysis.